(untitled) (International Journal of Physiotherapy, 2017)
Background: Headache is a common condition which physiotherapists have to deal with in clinical practice.Headaches which arise from the cervical spine are termed as Cervicogenic headaches (CGH), and these types of headaches are common form of a chronic and recurrent headache.The diagnostic criteria for CGH are outlined by the IHS (International Headache Society). The upper cervical joints, namely the occiput-C1 and C1-C2 segments are the most common origin of pain. Office and computer workers have the highest incidence of neck disorders than other occupations; the prevalence of neck disorders is above 50% among them. The purpose of this study is to find the effectiveness of Mulligan’s SNAG technique (C1-C2) and Maitland’s technique (C1-C2) in CGH and to compare these manual therapy techniques (Mulligan’s SNAG technique and Maitland’s technique) with a control group. Methods: 30 subjects were selected for the study among them 23 subjects completed the study. The subjects were randomly allocated to 3 groups. The range of motion (ROM) and severity of a headache were assessed pre and post intervention using FRT and HDI respectively. Result: The comparison revealed that SNAG group had a greater increase in cervical rotation (p<0.01) range than the Maitland’s technique and control groups. The mean value between pre-post differences shows a decrease in severity of headache among all three groups. The significant difference between 3 groups was found through Tukey’s post hoc test using ANOVA method (Group A versus Group C; p<0.01 and Group B versus Group C; p<0.05). Conclusion: The present study suggested that C1-C2 SNAG technique showed statistically significant improvement in reducing headache and disability when compared to the Maitland’s mobilization technique among cervicogenic headache subjects.